Determinan Status Pekerjaan Berdasarkan Tingkat Upah di Indonesia - Kukuh Arisetyawan; Ayu Padila (Jurnal Ekonomika : INDEPENDEN, 2025)
Job quality is a central concern in Indonesia’s labor development as the dominance of informal employment and wage inequality suggest that job creation has not always been accompanied by improvements in job quality. This study examines the determinants of employment status by wage level by classifying workers into three categories: informal (base outcome), low-wage formal, and high-wage formal. Using Indonesia’s National Labor Force Survey (SAKERNAS) 2023, the analysis covers 508,340 working-age individuals (≥15 years) with complete information. A multinomial logistic regression is employed and interpreted using average marginal effects. The results indicate that being male, having secondary and especially tertiary education, residing in urban areas, and working full-time increase the probability of high-wage formal employment. Persons with disabilities and part-time workers are less likely to access high-wage formal jobs and are more likely to remain in informal employment. Age exhibits a non-linear (inverted U-shaped) pattern, while the previous sector reflects labor market segmentation and skill mismatch. In conclusion, labor policy should prioritize not only job expansion but also job-quality upgrading through education, relevant skill development, inclusive formal job creation, and more even regional opportunities.